From spaces of sociability to spaces of political action: transfiguration of streets and squares into political spaces - Machado Filho, Guilherme Felix (Geografares, 2018)
In recent years, the world political scene has been agitated by numerous demonstrations that have shaken streets and squares, thus transfiguring, at certain moments, public spaces - public social spaces - in political spaces - spaces of political intentions. Therefore, this article aims to analyze this process of transfiguration from two perspectives of spatial analysis specific to political spaces: the organization of spaces and the exploration of their visibility. Taking as a reference the manifestations that occurred in Brazil in the period from 2015 to 2016, it was verified that the political use of streets and squares is not occasional, but the result of strategies defined by the protesting groups according to their own characteristics, as the theme of the manifestation , the number of people and the narrative to be created, and the spatial conditions found, such as visibility, size, accessibility and symbols present in these spaces.Keywords: political space, streets and squares, political manifestations, political action.